2018
DOI: 10.12691/jpar-3-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Activity across the Lifetime of Current Ultra-Endurance Exercisers

Abstract: This study describes the physical activity across and within the lifetime of current ultra-endurance exercisers. Participants (n = 115, % female = 42, age range 21 to 74 years) completed a modified version of the Lifetime Physical Activity Questionnaire (LPAQ) to assess physical activity over six life periods (5-12, 13-18, 19-30, 31-45, 46-60 and 61-75 years). Participants then were categorised into five groups according to which of these life periods they demonstrated the largest absolute increase in ultra-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Studies in the field of sports nutrition have stated that there is a relationship between lifetime ultra-endurance exercise and lifetime vegetable and fruit consumption. Meanwhile, ultra-endurance exercise was negatively related to the Western type of dietary pattern in the 19-30-year age group and positively related to the fruit and vegetable dietary pattern in the 31-45-year age group [50].…”
Section: Association Of Mediterranean Diet With Physical Activitymentioning
confidence: 92%
“…Studies in the field of sports nutrition have stated that there is a relationship between lifetime ultra-endurance exercise and lifetime vegetable and fruit consumption. Meanwhile, ultra-endurance exercise was negatively related to the Western type of dietary pattern in the 19-30-year age group and positively related to the fruit and vegetable dietary pattern in the 31-45-year age group [50].…”
Section: Association Of Mediterranean Diet With Physical Activitymentioning
confidence: 92%
“…This study includes a subset of participants from a previous study that reported on the lifetime physical activity [4] and diet [55] of current ultra-endurance exercisers. Ultra-endurance exercisers from the previous study were invited via email to take part in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The details of participant recruitment have been described elsewhere [4]. Briefly, participants were recruited internationally through Facebook, the Ultra Listserve (www.ultra@listserve.dartmouth.edu) and web pages associated with ultra-endurance organizations and events worldwide, including Australia, New Zealand, the United States of America and Canada.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations